Expanding Universe Illusion. (May 2019) - Phillips, David; Heard, Priscilla; Tyler, Christopher W.
We present a new induced movement illusion from global expansion or contraction in a triangular region filled with rising or falling textures. Objective global expansion or contraction induces lateral movement in the oblique edges of the triangle. The effects may be due to common and relative movements operating within a single texture.